Fishbone Diagram Dan Kerangka Pembuatan Roadmap Proses Digitalisasi Rekam Medis Di Rumah Sakit - Hendra; Tivani, Khoirun Nisa’; Narendra, Indra; Rohman, Hendra (Politeknik Kesehatan Bhakti Setya Indonesia, 2024)
Digitization of medical records in hospitals requires a series of activity implementation planning. Based on the grand design from the Ministry of Health, hospital HR, and SIMRS vendors that have existed previously, it can be used as a form of roadmap creation stages by making milestones as the basis for implementation. The roadmap creation uses a framework of thinking with a fishbone diagram as a cause and effect diagram, and with the methodology of using the project management life cycle. This study provides an overview of the process of digitizing medical records in supporting the implementation of RME so that RME can be implemented effectively, and considerations in decision making for the implementation of RME. The activities carried out include identification and analysis of the process of digitizing medical records, identification of supporting factors for digitizing medical records, and ending with creating a roadmap for digitizing medical records. The process of digitizing medical records requires 3 officers. Users of medical records who are not yet technologically proficient will be considered in the planning. The SOP must contain several things that need to be considered. The person in charge of the medical transfer section should have planned the budget needs. The budget submission is made at the annual meeting of the annual budget draft. Implementation of the priority scale by grouping active medical records into 3 groups. SIMRS needs to be developed and added features that can accommodate the results of medical record scans and features for scan control or the history scan menu. The medical record digitization roadmap stage 1 is HR planning, planning of infrastructure needs, designing digitalization procedures, and adjusting SIMRS features. Stage 2 is HR procurement, procurement of supporting infrastructure, establishing SOPs, and determining the priority scale of medical records. Stage 3 is a trial implementation of digitalization and evaluation of the trial. Stage 4 is the implementation of active medical record digitization.